Sustainable Agriculture, Forestry and Fisheries in the Bioeconomy - A Challenge for Europe - BRUNORI, GIANLUCA (EU Commission, 2015)
The 4th SCAR Foresight Exercise launched by the Standing Committee on Agricultural Research in spring 2014 explored the interactions between the primary sector and the bioeconomy. With an emphasis on the future, the exercise explored not only what will happen, but also what might happen by developing the paradigm of the bioeconomy, with the fundamental constraint of sustainability. Internal contradictions within primary production sectors and possible conflicts among sectors were a major point of interest. The report written by selected experts should help to set the research and innovation agenda, establish priorities, and provides ground for policies. The exercise was organised in a participative way involving the stakeholders from the beginning of the process facilitated by the European Commission (DG RTD Bioeconomy Directorate).